TOMPEL (TONG SAMPAH PENGHASIL ENERGI LISTRIK) - Bingesti Vegi Mayolan; Ade Chandra; Willy Azhar; Fitri Rahmatesa; Vebby Ola Handessa; Muhammad Imran Hamid (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
Plastic waste is the main problem that we face in Indonesia and still there is no appropriate way to solve it. Indonesia is ranked in number two as the country that throwing plastic waste to the sea. The common solution that mostly developed is by using recovery method, which is recycling the materials or compounds that exist in trash even it is physically, chemically, biologically or thermally. In this case it is needed a prototype for recovery system in changing trash into electrical energy. A prototype named TOMPEL (basket case generating electrical energy) has its function besides the place to put trashes but also has its function as converting tools to convert energy from plastic combustion into electrical energy with thermoelectricity system. The output is DC electricity that converts into AC electricity so it can be used after that. Based on experiment that has been done, the conclusion is effective plastic mass is 200 gram with outer voltage 10 volt by using glass wool as isolator. The voltage can recharge power in mobile phone. Moreover, solid waste is transformed into bricket.